Population pharmacokinetics and electrocardiographic effects of dihydroartemisinin–piperaquine in healthy volunteers. (16th August 2017) - Chotsiri, Palang; Wattanakul, Thanaporn; Hoglund, Richard M.; Hanboonkunupakarn, Borimas; Pukrittayakamee, Sasithon; Blessborn, Daniel; Jittamala, Podjanee; White, Nicholas J.; Day, Nicholas P.J.; Tarning, Joel
Abstract : Aims: The aims of the present study were to evaluate the pharmacokinetic properties of dihydroartemisinin (DHA) and piperaquine, potential drug–drug interactions with concomitant primaquine treatment, and piperaquine effects on the electrocardiogram in healthy volunteers. Methods: The population pharmacokinetic properties of DHA and piperaquine were assessed in 16 healthy Thai adults using an open‐label, randomized, crossover study. Drug concentration–time data and electrocardiographic measurements were evaluated with nonlinear mixed‐effects modelling. Results: The developed models described DHA and piperaquine population pharmacokinetics accurately. Concomitant treatment with primaquine did not affect the pharmacokinetic properties of DHA or piperaquine. A linear pharmacokinetic–pharmacodynamic model described satisfactorily the relationship between the individually corrected QT intervals and piperaquine concentrations; the population mean QT interval increased by 4.17 ms per 100 ng ml –1 increase in piperaquine plasma concentration. Simulations from the final model showed that monthly and bimonthly mass drug administration in healthy subjects would result in median maximum QT interval prolongations of 18.9 ms and 16.8 ms, respectively, and would be very unlikely to result in prolongation of more than 50 ms. A single low dose of primaquine can be added safely to the existing DHA–piperaquine treatment in areas of multiresistant Plasmodium falciparum malaria. Conclusions: Pharmacokinetic–pharmacodynamic modelling and simulation in healthy adult volunteers suggested that therapeutic doses of DHA–piperaquine in the prevention or treatment of P. falciparum malaria are unlikely to be associated with dangerous QT prolongation.